Awareness and recommendation of home blood pressure measurement among physicians in India: Results from Asia HBPM survey 2020 - Gurpreet Singh Wander; Ebtehal Salman; Noriko Matsushita; Narsingh Verma (Indian Heart Journal, 2023)
Background: Awareness of hypertension and blood pressure (BP) control rates are still low in India. Home blood pressure monitoring (HBPM) is recognized as a valuable tool to diagnose and support hypertension treatment including the prevention of cardiovascular diseases(CVD) and target organ damage. We explored the prevailing knowledge and current recommendation of HBPM in daily practice by physicians in India. Materials and methods: As part of Asia HBPM Survey 2020, a cross-sectional survey was conducted among healthcare providers from India between June 2020 to June 2021. The questionnaire consisted of 37 questions and sub-questions related to HBPM awareness and recommendations to patients. Results: A total of 832 physicians participated in the survey. Almost 83% were male, whereas age, specialty and workplace were well distributed. 31.3% of physicians instruct their patients to measure their BP before taking antihypertensive drugs, while around 30% of physicians gave no instructions. The reference value of hypertension diagnosis amongst the physicians was substantially low based on clinic BP (34.4%) and home BP (15.1%). Among physicians who manage hypertensive patients, nearly 88% recommend HBPM to their patients, however, only 34.9% of their patients own HBPM device and 30.4% of the patients measure their own BP at home. Conclusion: The survey reveals that HBPM instructions to the patients are either lacking or not well aligned with the local hypertension guidelines which may have led to the low HBPM use among patients. Clear and practical educational material and sessions are needed to improve the understanding of HBPM amongst physicians.